Plastic purge : how to use less plastic, eat better, keep toxins out of your body, and help save the sea turtles! - SanClements, Michael (St. Martin's Griffin, 2014)
"Plastic is everywhere you look. Our computers and children's toys are made out of it, and our water and slices of American cheese are packaged in it. But why is there so much and what is it doing to our bodies? Is it possible to use less plastic and be happier and healthier? In Plastic Purge, author Mike SanClements presents the history and science behind plastics, then teaches you how to cut down on the amount of plastic in your life. As an ecologist, SanClements has put together the most up-to-date and scientifically rigorous information available to explain how plastics release toxins into our bodies and the effect it has on us. Written with a casual, pop-science voice he provides easy-to-follow prescriptive advice for how to use less plastic, thereby reaping the benefits such as eating a healthier diet and living with less clutter. Dividing plastics into three separate categories: the good, the bad, and the ugly, SanClements shows you how to embrace the good (items like your phone or medical equipment), avoid the bad (i.e. food storage containers and toys that contain toxic chemicals like BPA and pthalates), and use less of the ugly (single-use plastic that's just plain wasteful)"--